John Anderson's data mining mission to Sumatra in 1823 : when method creates the object - Farish A. Noor (2014)
Today the term 'data mining' is used in both academic and non-academic circles through the practice is neither novel now new. This paper looks at the data collection mission led by John Anderson on behalf of the British East India Company in 1823, and considers if it is possible to collect dara in a purely objective, neutral manner. Though John Anderson was careful in his writing, and sought to communicate his findings in a dry, objective fashion, his own subject-position as a functionary working for the East India Conpany stands out in his account of the mission to Sumatra. This paper argues that the process of data collection is seldom ever a truly neutral enterprise, and that in the framing of the object of analysis , the cultural and socio-economic subject-position of the researcher/analysis . In this respect, an appraisal of Anderson's work today is also relevant for contemporary scholars who may likewise attempt an 'objective' approach to their work, and it reminds us that the method often constructs the object under scrunity.